ANALYSIS OF DIGITAL MARKETING STRATEGY IN IMPROVING IMPULSIVE BUYING BEHAVIOR OF MARKETPLACE CONSUMERS IN INDONESIA - Makarim, Siti Amirah; Dewi, Lati Sari (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the impact of digital marketing strategies specifically brand image and flash sale promotions on impulsive buying behavior among consumers in Indonesian marketplaces, with a particular focus on the Shopee platform. The research employs a descriptive quantitative approach, using purposive sampling techniques. Out of a population of 433 university students, 115 respondents were selected as the sample. Data analysis was conducted using SPSS version 26 and Microsoft Excel 2021. The results indicate that both brand image and flash sale promotions significantly influence consumer impulsive buying behavior, both partially and simultaneously. These findings highlight the importance of optimizing digital marketing strategies to enhance impulsive purchasing behavior in the e-commerce sector.